Analysis of Organizational Culture, Leadership Style, and Workload on the Performance of ASN Employees at the Dinas Perhubungan SUMUT - Nurmala, Nurmala; Yanti, Eli Delvi (Jurnal Fokus Manajemen, 2025)
This study aims to find the influence of organizational culture, leadership style, and workload on the performance of ASN employees at the North Sumatra Transportation Agency. The population in this study were all ASN employees at the North Sumatra Transportation Agency totaling 146 respondents. The number of samples taken was 59 people. The determination of the number of samples used in this study was determined using the Slovin formula because the population was more than 100. This study was conducted from 2025. Data collection was carried out using a questionnaire to produce primary-quantitative data which was then processed with SPSS version 25 with the multiple linear regression method. The results of the study showed that organizational culture, leadership style, and workload simultaneously had a positive and significant effect on ASN performance. Partially, these three variables also have a positive contribution to improving employee performance. A strong and adaptive organizational culture, a communicative and participatory leadership style, and a proportional division of workload have proven to be important factors in driving optimal ASN performance. The results of the determination coefficient test of 91.8% of ASN employee performance can be explained and obtained from the variables of organizational culture, leadership style and workload, while the remaining 8.2% is influenced by other factors.